The Clinical Significance of Autoantibodies in Hepatitis C Patients Submitted to Interferon Treatment - Rodrigues-Pinto,Eduardo (2015)
Hepatitis C virus is associated with several immune-mediated phenomena, presented usually as extra-hepatic hepatitis C manifestations. A predisposition to autoimmunity associated with the presence of baseline autoantibodies has been demonstrated in interferon mediated autoimmune diseases. We report a male patient, 34 years old, with genotype 1, chronic hepatitis C (hepatitis C viremia 1.432.463 UI/mL) and family history of psoriasis. He had high levels of transaminases and immunology showed positive antinuclear antibodies (1/320) and anti-smooth-muscle antibodies, with elevated immunoglobulin G (1740 mg/dL). Liver biopsy revealed a F1/2 Metavir score, histologic activity index of 3 and mild piecemeal necrosis. Antiviral treatment was started with peg-interferon a2a 180 mcg plus ribavirin 1200 mg, and the patient had rapid virologic response, normalization of transaminases, negativation of antinuclear antibodies positivity and decrease of immunoglobulin levels. However, at week 22, he developed psoriatic-like eczema and arthritis with functional limitation. Due to suspicion of latent psoriatic arthritis not previously diagnosed, he was started on methotrexate 10 mg/weekly with improvement of psoriatic plaques, arthritis and functional limitation. Patient achieved sustained virologic response, with normal transaminases and no significant changes in immunology. Post-treatment median hepatic elastography was 3.6 kPa. Autoimmunity in hepatitis C infection is not limited to surrogate autoantibody seropositivity, but may embrace the full spectrum of autoimmune disorders.